Accounting earnings and future economic rents - Ahmed, Anwer S. (Journal of Accounting and Economics, 1994)
This study reexamines competition, cost structure, and growth opportunities effects on earnings response coefficients and extends this literature in several ways. First, it presents a more refined theoretical motivation for investigating competition and cost structure effects. Second, it introduces new economic factor proxies that confirm prior findings with respect to competition but differ from prior findings with respect to cost structure and growth opportunities. Overall the evidence suggests that accounting earnings reflect information about future economic rents generated by firms' assets-in-place. The evidence also suggests, contrary to prior studies, that accounting earnings are not very informative about firms' growth opportunities.